Thomas Paine and the literature of revolution - Larkin, Edward (Cambridge University, 2013)
This text not only addresses the problem that scholars have tacitly agreed not to treat Thomas Paine as a literary figure, but also demonstrates that his literary sensibility is particularly evident in the very texts that confirmed his importance as a theorist.